Regulation Issues of Digital Broadcasting in Job Creation Law - Supadiyanto Supadiyanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
Broadcast media had become a prospective business. The practice of the broadcast media business had surpassed legislation authority, resulting in currently utilized technology unaccommodated in Law No. 32/2002 on Broadcasting. The release of Law No. 11/2020 on Job Creation to merge existing laws into a simple regulation package did not make the broadcast media industry visionary. How are the current law maps of analog and digital broadcasting in Indonesia? How is the current practice of digital broadcast media business in Indonesia? The type of research is descriptive. This study used a legal positivism approach. The data collecting technique was conducted through literature study and legal study. As for the result, the current analog broadcasting regulation complied with Law No. 32/2002 concerning Broadcasting and Law No. 11/2020 concerning Job Creation. In practice, TV stations that broadcast on digital-internet channels did not possess a formidable legal basis.